2009
DOI: 10.1016/j.bpj.2008.12.1294
|View full text |Cite
|
Sign up to set email alerts
|

The Role Of Mineralocorticoid Receptors In The Adaptation Of Cardiac Myocytes To Pregnancy

Abstract: Ventricular fibrillation (VF) is the main cause of sudden cardiac death. We hypothesized that VF induced by large scars in an isolated porcine heart model could aid the understanding of VF in human hearts associated with structural disease. The explanted hearts were perfused with blood and Tyrode solution at 37C, and optically imaged with a voltage-sensitive fluorescence dye (di4-ANEPPS excited at 530nm with 150W halogen lamp). The emitted signal was filtered (610nm) and recorded with high speed cameras (MiCAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These findings prompted our investigation of the possible contribution of the sodium pump inhibition to cardiac adaptations during pregnancy. Our previous work (Bassien-Capsa et al 2006) showed that pregnancy is characterized by a metabolic remodelling of the maternal heart and adaptations of haemodynamic and cardiac parameters, including cardiomyocyte dimensions. We demonstrated adaptive hypertrophic remodelling of the heart, as well as of its cells, during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings prompted our investigation of the possible contribution of the sodium pump inhibition to cardiac adaptations during pregnancy. Our previous work (Bassien-Capsa et al 2006) showed that pregnancy is characterized by a metabolic remodelling of the maternal heart and adaptations of haemodynamic and cardiac parameters, including cardiomyocyte dimensions. We demonstrated adaptive hypertrophic remodelling of the heart, as well as of its cells, during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular (LV) myocytes were isolated after retrograde perfusion of the heart with proteolytic enzymes, as described previously (Chorvatova et al 2004;Bassien-Capsa et al 2006). Myocytes were maintained in storage solution at 4 • C until used.…”
Section: Cell Isolationmentioning
confidence: 99%
See 1 more Smart Citation